2020
DOI: 10.1002/dmrr.3367
|View full text |Cite
|
Sign up to set email alerts
|

High TG to HDL ratio plays a significant role on atherosclerosis extension in prediabetes and newly diagnosed type 2 diabetes subjects

Abstract: Aims We investigated the role of TG to HDL ratio (TG/HDL) on atherosclerosis extension, defined as presence of coronary artery calcium (CAC), carotid and femoral plaque, in prediabetes or newly diagnosed type 2 diabetes (T2D). Methods We performed a retrospective, cross‐sectional, single centre study involving 440 prediabetes or newly diagnosed controlled T2D subjects. Participants underwent CAC analysis by computed tomography and carotid and femoral plaque evaluation by ultrasonography and were stratified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 53 publications
2
43
0
1
Order By: Relevance
“…Therefore, we evaluated the possible impact that an altered lipid profile or lipid lowering and antihypertensive therapies could have on mitokine levels. We first subdivided T2D patients on the basis of the triglycerides/HDL (TG/HDL) ratio, known to be associated to insulin resistance and cardiovascular disease in T2D [ 49 , 50 ]. We found that patients with high TG/HDL ratio have higher level of GDF15 and FGF21 (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we evaluated the possible impact that an altered lipid profile or lipid lowering and antihypertensive therapies could have on mitokine levels. We first subdivided T2D patients on the basis of the triglycerides/HDL (TG/HDL) ratio, known to be associated to insulin resistance and cardiovascular disease in T2D [ 49 , 50 ]. We found that patients with high TG/HDL ratio have higher level of GDF15 and FGF21 (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, TG/HDL was often used to evaluate insulin resistance [34][35][36][37][38]. Recent studies have found a correlation between TG/HDL and the incidence of diabetes [39][40][41][42]. However, these studies did not include patients with prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Non-HDL cholesterol (non-HDL-C) was derived from baseline values. HbA1c was measured with high-performance liquid chromatography using a National Glycohemoglobin Standardization Program and standardized to the Diabetes Control and Complications Trial assay [32]. Chromatography was performed using a certified automated analyzer (HPLC; HLC-723G7 hemoglobin HPLC analyzer; Tosoh Corp.; normal range 4.25-5.9% [23-41 mmol/mol]).…”
Section: Biochemical Analysismentioning
confidence: 99%